Constructing politicized national identities: identity positioning by US, China, and Philippine opinion editorials on the Scarborough Shoal conflict - Montiel, Cristina J (Archīum Ateneo, 2019)
How do newspapers’ opinion editorials produce national identities of nations involved in an international conflict? This study examines op-eds in the US, China and the Philippines, which discuss the Scarborough Shoal conflict. Data processing includes word-association calculations and positioning analysis. Results demonstrate self-vested national identities. China-based articles create national identities around the goal of preserving political clout in the Asia-Pacific. US op-eds invert China’s goal and generate identities asserting US regional power. Philippine commentaries portray China as a bully and the US as a defender. Results are discussed in light of the link between politicized national identities and global clashes.